2021
DOI: 10.3389/fmed.2021.665247
|View full text |Cite
|
Sign up to set email alerts
|

The Weekend Drug; Recreational Use of Sildenafil Citrate and Concomitant Factors: A Cross-Sectional Study

Abstract: Background: Men who use erectile dysfunction medications for recreational purposes may be at increased risk of becoming psychologically dependent, which in turn could lead to psychogenic-based erectile dysfunction symptoms. Sildenafil has become one of the most commonly prescribed and abused drugs available today.Objectives: This study aimed to describe the utilization pattern and associated factors of sildenafil citrate among its users visiting community pharmacies in Gondar, Ethiopia.Methods: A facility-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…A recent cross-sectional study of community pharmacies in Ethiopia showed that 66.2% of oral PDE5i use is for recreational purposes. 23 It is unclear if the drug was obtained under the treatment of a physician or not in our set of cases. However, our results favor the highly selected use of these products for the enhancement of erection in adolescents, given that priapism at a young age potentially has everlasting impacts on sexual health.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent cross-sectional study of community pharmacies in Ethiopia showed that 66.2% of oral PDE5i use is for recreational purposes. 23 It is unclear if the drug was obtained under the treatment of a physician or not in our set of cases. However, our results favor the highly selected use of these products for the enhancement of erection in adolescents, given that priapism at a young age potentially has everlasting impacts on sexual health.…”
Section: Resultsmentioning
confidence: 96%
“…22 As of today, no PDE5i is approved for the treatment of ED in adolescents; nevertheless, its recreational use has been reported by some studies. [23][24][25][26] In a survey of 43 teenage males who self-identified as "lifetime sildenafil citrate users," it was shown that as many as 9% had started abusing the product since the age of 14 and that curiosity and peer pressure were the two most frequent contributory factors for the initial use. 24 In our study, sexual dysfunction was also among the top indications for using PDE5i in the 12-18 age group.…”
Section: Resultsmentioning
confidence: 99%
“…But even after 24 years since its approval by FDA, the question remains unanswered: Is the use of sildenafil worth the risks and addiction associated with it? Multiple studies have shown the increasing recreational use of sildenafil, especially in younger men who preferably use this pharmacotherapy for pleasing their partners rather than treating ED [ 3 , 4 ]. Besides its use in sustaining an erection, it is also an FDA-approved drug for treating pulmonary arterial hypertension (PAH) because of its vasodilation effect.…”
mentioning
confidence: 99%
“…The stigma associated with erectile dysfunction is a major reason for its misuse. The easy availability of this inexpensive drug has also contributed to the increasing demand [ 3 ]. The use of sildenafil along with other designer drugs e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation